EZH2-targeted therapies in cancer: hype or a reality - Eich, Marie-Lisa (Cancer Res, 2020)
Next-generation genomic sequencing has identified multiple novel molecular alterations in cancer. Since the identification of DNA methylation and histone modification, it has become evident that genes encoding epigenetic modifiers that locally and globally regulate gene expression play a crucial role in normal development and cancer progression. The histone methyltransferase enhancer of zeste homolog 2 (EZH2) is the enzymatic catalytic subunit of the polycomb repressive complex 2 (PRC2) that can alter gene expression by trimethylating lysine 27 on histone 3 (H3K27). EZH2 is involved in global transcriptional repression, mainly targeting tumor suppressor genes. EZH2 is commonly overexpressed in cancer and shows activating mutations in subtypes of lymphoma. Extensive studies have uncovered an important role for EZH2 in cancer progression and have suggested that it may be a useful therapeutic target. In addition, tumors harboring mutations in other epigenetic genes such as ARID1A, KDM6, and BAP1 are highly sensitive to EZH2 inhibition, thus increasing its potential as a therapeutic target. Recent studies also suggest that inhibition of EZH2 enhances the response to tumor immunotherapy. Many small molecule inhibitors have been developed to target EZH2 or the PRC2 complex, with some of these inhibitors now in early clinical trials reporting clinical responses with acceptable tolerability. In this review, we highlight the recent advances in targeting EZH2, its successes and potential limitations, and we discuss the future directions of this therapeutic subclass.